Exercise during pregnancy modulates infant cellular and whole‐body adiposity - Alex Claiborne; Filip Jevtovic; Donghai Zheng; Cody Strom; Breanna Wisseman; Samantha McDonald; Edward Newton; Steven Mouro; James DeVente; Joseph A. Houmard; Nicholas T. Broskey; Linda E. May (Physiological Reports)
Abstract Non‐pharmaceutical interventions are needed to target the growing intergenerational cycle of obesity. We aimed to determine whether in utero exposure to different exercise doses during pregnancy directly reduces infant cellular and whole‐body adiposity. Pregnant women completed ~24 weeks of supervised exercise training; for standardization of exercise analysis (frequency, intensity, time, and volume‐FIT‐V), metrics were assessed from 16 to 36 weeks. Mesenchymal stem cells (MSC) collected from the umbilical cord at delivery underwent 21 days of adipogenic differentiation, then Oil Red O staining for lipid content. Infant body composition was measured at 1 month of age. ANCOVA and Pearson correlations determined the influence of prenatal exercise on infant adiposity. Exercise decreased infant MSC lipid content (p = 0.01) and body fat percentage (p = 0.009) irrespective of dose. Total exercise volume throughout pregnancy was negatively correlated with infant body fat % (R2 = 0.31, p = 0.02) due to lower subscapular skinfolds (R2 = 0.30, p = 0.02), while weekly exercise duration influenced adipogenic MSC lipid accumulation (R2 = −0.23, p = 0.03) and BF% (R2 = −0.15, p = 0.01). In utero exposure to exercise reduced cellular and whole‐body infant adiposity in a dose‐dependent manner.